THE EFFECT THE EFFECT OF SIDE OBSTACLES ON TRAFFIC FLOWS (Case Study of Prof. A. Majid Ibrahim Street, Sigli City): Side Barriers, PKJI 2014, Urban Road - Rini Astuti Rini (SainsTech Innovation Journal, 2022)
The high value of side barriers on a road segment will cause a decrease in traffic flow. The purpose of this study was to determine the factors that affect the decrease in the smooth flow of traffic in some side barriers conditions. The research includes a survey on traffic volume, vehicle speed, and side barriers. The study was conducted for 7 days. The research location is on Jalan Prof. A. Majid Ibrahim Sigli City, The length of the research site segment is 350 meters. From the survey results obtained data which will then be calculated using the Indonesian Road Capacity Guidelines (PKJI 2014) for urban roads. From the survey data and then processed using the 2014 PKJI guidelines, the highest traffic flow on Sundays was 785.1 cur/hour. The average vehicle speed is 25.28 km/hour, the side drag weight is 875.06 with a high side drag class (T), the road segment capacity (C) is 2,597.25 skr/hour, the degree of saturation (DJ) is 0.30 and the level of saturation is 0.30. road service B, namely the condition of stable traffic flow, but the speed of operation is starting to be limited by traffic conditions.